Home-administered transcranial direct current stimulation is a feasible intervention for depression: an observational cohort study - Charvet, Leigh; George, Allan; Charlson, Erik; Lustberg, Matthew; Vogel-Eyny, Amy; Eilam-Stock, Tehila; Cho, Hyein; Best, Pamela; Fernandez, Luis; Datta, Abhishek; Bikson, Marom; Nazim, Kamran; et al. (Frontiers in Psychiatry, 2023)
Transcranial direct current stimulation (tDCS) is an emerging treatment for major depression. We recruited participants with moderate-to-severe major depressive episodes for an observational clinical trial using Soterix Medical's tDCS telehealth platform as a standard of care. The acute intervention consisted of 28 sessions (5 sessions/week, 6 weeks) of the left anodal dorsolateral prefrontal cortex (DLPFC) tDCS (2.0 mA × 30 min) followed by a tapering phase of weekly sessions for 4 weeks (weeks 7–10). The n = 16 completing participants had a significant reduction in depressive symptoms by week 2 of treatment [Montgomery–Åsberg Depression Rating Scale (MADRS), Baseline: 28.00 ± 4.35 vs. Week 2: 17.12 ± 5.32, p < 0.001] with continual improvement across each biweekly timepoint. Acute intervention responder and remission rates were 75 and 63% and 88 and 81% following the taper period (week 10).